Abnormalities of insulin and growth hormone secretion in children with coeliac disease. Issue 1 (January 1973) - Day, Gillian; Evans, Kenneth; Wharton, Brian
Abstract : The effect of intravenous tolbutamide on plasma levels of glucose, cortisol, growth hormone, and insulin, and the effect of oral Bovril on plasma growth hormone have been studied in 10 children with coeliac disease and 6 children who, though small, had normal jejunal morphology (`controls'). The growth hormone and insulin responses to tolbutamide in the children with coeliac disease were significantly smaller than in the controls. Growth hormone response to Bovril was normal in most of the children but 3 of them with coeliac disease failed to achieve a satisfactory response in growth hormone levels after both tolbutamide and Bovril. These results cannot be explained by malnutrition or by inadequate hypoglycaemia during tolbutamide stimulation, and a convincing hypothesis to explain them has not been formulated. Clinically, though tests of other conventional stimuli of growth hormone and insulin production require study, the diagnosis of coeliac disease should actively be considered in any child with low levels of insulin and growth hormone. These observations may partly explain the association of coeliac disease and diabetes mellitus.